(untitled) (Salud, Arte y Cuidado, 2019)
The purpose of this essay is to make a reflection from a gender perspective, about the demands of today’s world that Venezuelan women face in public and private spaces, namely; in the world of work and domestic-family work, affecting their quality of life and that of their family group. These considerations have been accompanied by some revisions of statistical data that reveal the present situation of the structure of the Venezuelan family, demonstrating that, despite the great efforts of modernity, it continues to hegemonically impregnated by the patriarchal model, thus being reflected in the rest of society, typical of its socio-historical process. Through this analysis, a call for attention to Venezuelan society is made to: a) recognize the contradictions of its demands in public space and private space today, b) overcome the patriarchal model, as it avoids the necessary emancipation that These times demand and c) promote a cultural pattern of upbringing that transforms the family structure, which is oriented towards a better quality of life.